MENYIAPKAN TENAGA KERJA YANG BERKARAKTER MELALUI PENDIDIKAN DAN PEMBELAJARAN VOKASI - Ade CH Gultom (Universitas Negeri Medan, 2016)
Character education is not just learning knowledge alone, but involves moral, ethical values, aesthetics, manners and noble character, and so forth. Related to this, the field of vocational education that prepares culinary industry sector workforce, need to review the learning and assessment of learning outcomes that had been done in the classroom into practice the spirit of vocational education. review aims to re-examine whether subjects in the practice already implicitly implement character education. Through a review of all of the components are expected to practice learning from planning, implementation, and assessment of learning are already referring to character education. Vocational education can apply the teaching model of social partners in learning and group investigation in order to develop students' character as an adult. Developed individual character covers four aspects, namely the liver though, if thought, sports, though the flavor, and intention. Therefore, assessment of learning outcomes in vocational education should include aspects of the character. Assessment aspect of the character is done through three stages. First, identify what are the components of characters that need to be assessed. Second, aspects of character assessment as a result of the learning process is done on-going assessment. Third, assessment of learning outcomes aspects of character refers to the concept of character education. For the successful development of the required exemplary character of the teachers and other personnel as the main prerequisite.Kata Kunci: Pembelajaran, Penilaian, Pendidikan Vokasi, Karakter